Tau kinetics in Alzheimer's disease - Hier, Daniel B.; Azizi, Sima; Thimgan, Matthew S.; Wunsch, Donald C. (Frontiers in Aging Neuroscience, 2022)
The cytoskeletal protein tau has been implicated in the pathogenesis of Alzheimer's disease. In Alzheimer's disease, intra-neuronal neurofibrillary tangles contain abnormally phosphorylated insoluble tau. Levels of soluble tau are elevated in the brain, the CSF, and the plasma of patients with Alzheimer's disease. To better understand the causes of these elevated levels of tau, we propose a three-compartment kinetic model (brain, CSF, and plasma). The model assumes that the synthesis of tau follows zero-order kinetics (uncorrelated with compartmental tau levels). The model assumes that the release, absorption, and clearance of tau is governed by first-order kinetics (linearly related to compartmental tau levels). Tau that is synthesized in the brain compartment can be released into the interstitial fluid, catabolized, or retained in neurofibrillary tangles. Tau released into the interstitial fluid can mix with the cerebrospinal fluid and drain to the blood. Most soluble tau is in the brain compartment and only minute amounts are released into the CSF compartment to eventually reach the plasma. Losses of tau in the drainage pathways are estimated to be as high as 90%. The kinetic model allows for an estimation of the half-life of tau in each compartment (552 hr in the brain, 9.9 hr in the CSF, and 10 hr in the plasma). The kinetic model predicts that an increase in the neuronal tau synthesis rate or a decrease in tau catabolism rate best accounts for increased tau levels in the brain, CSF, and plasma. Furthermore, the model predicts that any increases in brain half-life of tau in Alzheimer's disease should be attributed to decreased tau catabolism and not to increased tau synthesis. Most tau turnover in the neuron occurs through catabolism rather than release to the CSF compartment. Additional experimental data would make the ascertainment of the model parameters more precise.